Between scripture and human reason: an intellectual biography of Muḥammad ibn Ismāʿīl al-Bukhārī (d.256/870) - Abu Alabbas, B (2018)
By the dawn of the fifth/eleventh century, al-Bukhārī (d. 256/870) was recognized as the most highly regarded hadith scholar and his Ṣaḥīḥ as the most authoritative book, after the Qurʾan. This canonical status promoted a romanticized version of al-Bukhārī that does not reflect the reality that his pre-canonical historical record presents. This study recovers the reality of al-Bukhārī and provides a critical biography of him, tracing the progress of his career and detailing the objectives of his work. It provides a re-assessment of al-Bukhārī’s own juridical, theological, and hadith-criticism principles based on an analysis of his own works, arguing that al-Bukhārī was shaped by the split between hadith and raʾy. It distinguishes three stages in his career: early education under raʾy authorities, conversion to hadith-based school, and his critique of the raʾy-based scholars in Transoxania. Al-Bukhārī was a significant contender of theology and law in his own day and certainly promoted a moderate position in theology and law that proved crucial to his future renown. He appears to have been Medinese in law and Iraqi in hadith criticism. His legal theory adopts some of Mālik ibn Anas’ (d. 179/795) views and al-Shāfiʿī’s (d. 204/820) hermeneutical concepts. His legal method and positive law appear to be systematically anti-raʾy and exhibit a virulent disparage of Abū Ḥanīfa (d. 150/767) and al-Shaybānī (d. 192/804-5). It appears that al-Bukhārī composed the Ṣaḥīḥ over a long period, at least a decade, as the Ṣaḥīḥ itself tends to confirm a chronological progress. This progress, the author contends, was the outcome of al-Bukhārī’s long project in Transoxania, combating raʾy and promoting hadith. Al-Bukhārī achieved prominence within hadith-based circles for his unique transmitter-criticism (rijāl) works, particularly al-Tārīkh, but when he conceded that one’s utterance (lafẓ) of the Qurʾan is created, he was immediately denounced by the hadith-based school. This controversy caused the collapse of al-Bukhārī’s career, leading to his demise in Khartank near Samarqand in 256/870.